FAKTOR – FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK BAGI WAJIB PAJAK ORANG PRIBADI DI KOTA KEDIRI - Sugeng, Sugeng; Nurdiwati, Diah; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2017)
Awareness of the tax is the most important in the collection of taxes. The cause of a lack of willingness among others, are the principles of taxation, namely that the results of the indirect taxation enjoyed by taxpayers. This study aims to assess the Factors Affecting the willingness to pay taxes, among others, is the realization of paying tax knowledge, understanding tax laws, and a good perception of the effectiveness of the tax system. This research was conducted by distributing questionnaires to taxpayers who are having registered on KPP Pratama Kediri. Once the data is collected, the data were analyzed using the program to test whether the model used in this study is quite appropriate as a model analyzed. Then use the method of analysis with software Partial Least Square, which SmartPLS. Models in PLS consists of three models, the models inner, outer model, and weight relation (Ghozali, 2006) to examine the relationship between variables. According to the research conducted by the authors later discovered that 2 (two) variables have a significant influence on the willingness to pay taxes be seen from the t-statistic greater than 2 (two) is variable consciousness of paying taxes and variable knowledge and understanding of the taxpayer. Meanwhile, 1 (one) variable has no significant effect on the willingness to pay taxes, namely the perception that baik.Penelitian aims to provide insight to related parties are faced with the expansion and intensification of business tax. And for it requires hard work from the Tax Office to make socialization harder to taxpayers, increasing awareness of taxpayers and a good perception of the tax system. Therefore, it can help to increase the willingness of taxpayers to pay taxes.